2005
DOI: 10.1055/s-2005-861421
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Surveillance of Chronic Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease, ulcerative rectocolitis and Crohn's disease are a major public health problem. The incidence of ul− cerative rectocolitis (UC), which has remained stable since the early eighties, is around 10 per 100 000 inhabitants [1]. Crohn's disease (CD) appears to be on the increase, with a global inci− dence of 5.6 / 100 000 [1]. These diseases are associated with a risk of digestive cancer, which justifies regular endoscopic sur− veillance. Unfortunately, there is no properly−defined code fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…These observations led to the first endoscopic surveillance program for patients with UC [132], which became emulated widely and has now become the standard of care for those patients with UC and CC who are at high risk for CRC [19, 20, 133, 134]. As a result of such surveillance, evidence has been found supporting the role of dysplasia in the pathogenesis of CRC in IBD and can be summarized as follows: first, studies of resected colons have shown that dysplasia occurs in proximity to cancer in approximately 90% of resected colons, including nearly all cases with multiple cancers [72, 125, 129, 135, 136] and elsewhere in the colon in approximately 75% of cases with UC [76, 125, 127, 137] and 27% to 100% of cases of CC [136, 138].…”
Section: Colorectal Neoplasia In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations led to the first endoscopic surveillance program for patients with UC [132], which became emulated widely and has now become the standard of care for those patients with UC and CC who are at high risk for CRC [19, 20, 133, 134]. As a result of such surveillance, evidence has been found supporting the role of dysplasia in the pathogenesis of CRC in IBD and can be summarized as follows: first, studies of resected colons have shown that dysplasia occurs in proximity to cancer in approximately 90% of resected colons, including nearly all cases with multiple cancers [72, 125, 129, 135, 136] and elsewhere in the colon in approximately 75% of cases with UC [76, 125, 127, 137] and 27% to 100% of cases of CC [136, 138].…”
Section: Colorectal Neoplasia In Ibdmentioning
confidence: 99%
“…Ideally, the rationale of surveillance is to allow most patients whose biopsy specimens remain free of dysplasia to avoid colectomy while enabling those with dysplasia to undergo surgery before the development of CRC. Although validation of this strategy has been based largely on indirect evidence, surveillance has been widely embraced and broadly implemented as the standard of care for patients at risk for CRC [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…The guidelines regarding the surveillance of CRC in UC can be summarized as follows: (i) Regular surveillance should begin after 8–10 years for pancolitis and after 15–20 years for left‐sided disease; (ii) There should be a decrease in the screening interval with increasing disease duration; (iii) Two to four random biopsy specimens, every 10 cm, should be taken from the entire colon, with additional samples of suspicious areas and (iv) Patients with primary sclerosis cholangitis represent a subgroup at higher risk 1–3 …”
Section: Guidelines Dysplasia and Adherencementioning
confidence: 99%
“…Different societies have published guidelines for the surveillance of colorectal cancer (CRC) in ulcerative colitis (UC) 1–3 . These guidelines are very similar and very few variations are observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, some data indicate that surveillance programs are beneficial for the patient in respect to mortality from CRC (912). Moreover, even if there is no clear and undisputed evidence of the efficacy of surveillance, several authorities and guidelines advocate such a strategy (1316).…”
Section: Introductionmentioning
confidence: 99%